2022
DOI: 10.3390/plants11192608
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect and Potential Risk of Pantoea on Rice Production

Abstract: Bacteria from the genus Pantoea have been reported to be widely distributed in rice paddy environments with contradictory roles. Some strains promoted rice growth and protected rice from pathogen infection or abiotic stress, but other strain exhibited virulence to rice, even causing severe rice disease. In order to effectively utilize Pantoea in rice production, this paper analyzed the mechanisms underlying beneficial and harmful effects of Pantoea on rice growth. The beneficial effect of Pantoea on rice plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 142 publications
0
8
0
Order By: Relevance
“…Although the genus Pantoea is known as a phytopathogen, studies are reported in which they have a beneficial effect on plants, especially in promoting growth and controlling phytopathogens (Lorenzi et al., 2022; Lv et al., 2022; Pusey, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although the genus Pantoea is known as a phytopathogen, studies are reported in which they have a beneficial effect on plants, especially in promoting growth and controlling phytopathogens (Lorenzi et al., 2022; Lv et al., 2022; Pusey, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Anjum and Chandra [34] have already reported isolation from stevia plants of the bacteria belonging to the genus Pantoea, although species identification was not performed in that work. Originally, Pantoea was known as a plant pathogen; however, today, it is generally known that these bacteria have a beneficial effect on plants, especially in growth promotion and phytopathogen control [53][54][55][56]. P. vagans is very often isolated together with P. agglomerans since both species occupy the same ecological niches, and even some isolated P. vagans strains were previously identified as P. agglomerans [57].…”
Section: Discussionmentioning
confidence: 99%
“…The nitrogen fixation by bacterial species such as Azotobacter , Clostridium , or Rhizobium has been reported to be of vital importance in plant growth [ 118 ]. Some of the genera found exclusively in the plant tissues like Pseudomonas [ 119 ], Pantoea [ 120 ], and Siccibacter [ 121 ] have been associated with nitrogen fixation and auxin biosynthesis [ 122 ]. It should be noted that rhizobacteria such as Bacillus amyloliquefaciens and Pseudomonas putida can promote the activation of the jasmonic acid and salicylate acid pathway, which increases the resistance levels to insects such as caterpillars [ 123 ].…”
Section: Discussionmentioning
confidence: 99%